“Seismic Behavior of Torsional & Mass Irregularity Due to Consideration of Tuned Mass Damper at Different Position of Building” - Reena Sahu, Pradeep Kumar Ghosh, Anurag Wahane, Sri Ram Krishna Mishra, Sanket Shrivastava (Mathematical Statistician and Engineering Applications, 2023)
The study is to investigate the seismic behavior of RC building having tuned mass damper at the different position. The first phase of work is to analyze the RC building having mass damper at the center and random eccentric position of 5th, 7th, and 9th Storey. The second phase of works is to validate the torsional and mass irregularity coefficient factor. Non-linear Time History Analysis is used for the identification of behavior of building. The seismic intensity of Zone -V is applied in the structure. The seismic response such as displacement, storey shear is been evaluated. The result shows that there is no torsional effect for the damper located at the center. Thus, concluded that for the structural safety of building, the damper should be placed centrally at the topmost storey.